Low-carbon high-performance Al-Mg-Si-RE aluminum alloy for forging and preparation method thereof

CN123027488APending Publication Date: 2026-11-03ZHEJIANG JINFEI KAIDA WHEEL
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611460213.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-20
Publication Date
2026-11-03

AI Technical Summary

Technical Problem

Existing technologies cannot achieve the balance between low-carbon and high-performance forged aluminum alloys by precisely controlling the composition of Fe impurities to transform them into nanoscale dispersed strengthening phases under conditions of high proportion of recycled aluminum feeding. This makes it impossible to meet the high strength, toughness, and fatigue performance requirements of load-bearing components such as wheel hubs for new energy vehicles.

Method used

By matching the Fe content with the ratio of multiple microalloying elements such as Mn/Cr/La/Ce/Ni/Ti, the Fe impurities introduced by recycled aluminum are transformed into nanoscale spherical dispersed strengthening phases. Combined with high proportion of recycled aluminum melting and casting, multi-stage melt purification, gradient homogenization heat treatment, precision forging and T6 aging treatment, Al-Mg-Si-RE aluminum alloy is prepared.

Benefits of technology

With a high proportion of recycled aluminum (over 50%), the forged aluminum alloy achieves a balance between high strength and high toughness, meeting the performance requirements of load-bearing components such as wheel hubs for new energy vehicles, reducing production energy consumption and carbon emissions, and demonstrating significant environmental and economic benefits.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123027488A_ABST
    Figure CN123027488A_ABST
Patent Text Reader

Abstract

This invention discloses a low-carbon, high-performance Al-Mg-Si-RE aluminum alloy for forging and its preparation method. The alloy composition includes Si, Mg, Cu, Fe, Mn, Cr, La, Ce, Ni, and Ti, with the balance being Al and unavoidable trace impurities. The core design involves two levels of Fe content control: Mg / Si = 1.25–1.50; when Fe is 0.12%–0.30%, Fe / (Mn+Cr) = 0.31–0.60, and the total La+Ce+Ni+Ti content is 0.08%–0.12%; when Fe is greater than 0.30% but not greater than 0.40%, Fe / (Mn+Cr) = 0.70–1.05, and the total La+Ce+Ni+Ti content is 0.13%–0.18%. The preparation process includes recycled material pretreatment, melting and refining, semi-continuous casting, three-stage homogenization, three-step closed-die forging, and T6 heat treatment. This invention, with a recycled aluminum content ≥50%, can transform harmful Fe impurities into 100nm-200nm spherical dispersed strengthening phases, increasing the tensile strength of T6 state forgings. R m ≥350MPa, specified plastic elongation strength R p0.2 ≥315MPa, elongation after fracture A With a carbon content of ≥12%, it combines low carbon properties with high strength and high toughness, making it suitable for load-bearing forgings such as wheel hubs and suspension control arms for new energy vehicles.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of aluminum alloy material technology, specifically relating to a low-carbon, high-performance Al-Mg-Si-RE aluminum alloy for forging and its preparation method. It can be widely used in load-bearing forged parts such as wheel hubs and suspension control arms of new energy vehicles, and is especially suitable for low-carbon forged aluminum alloy production scenarios using a high proportion of recycled aluminum as raw material. Background Technology

[0002] The automotive industry is accelerating its transformation towards lightweighting, electrification, and low carbon emissions. New energy vehicles generally use large-capacity power batteries, integrating numerous lithium-ion battery modules into their chassis, significantly increasing overall vehicle weight—mainstream models typically have a curb weight between 1.8 and 2.5 tons. To improve vehicle dynamic response and handling stability, the unsprung mass of the suspension system must be strictly controlled; simultaneously, the drive motor's instantaneous high torque output characteristics require tires with excellent longitudinal grip. While low-profile tires help enhance steering precision and lateral stiffness, they simultaneously weaken the tire's energy absorption capacity, resulting in a significantly narrower effective compressibility margin. When encountering moderate-intensity road impacts, the tires may quickly reach their compression limits, directly transferring the impact load to the wheel hub and suspension structure, potentially causing plastic deformation of the wheel hub or even structural damage. Compared to cast wheels, forged wheels offer systematic advantages in comprehensive mechanical properties, quality characteristics, and manufacturing precision: higher specified ductile strength and fracture toughness, a better power-to-weight ratio, a longer service life, and stricter dimensional and positional tolerance control. Cast wheels are mostly produced using gravity casting or low-pressure casting processes, which may result in inherent defects such as porosity and shrinkage in the microstructure. Forged wheels, on the other hand, utilize multi-directional hydraulic forging equipment capable of handling tens of thousands of tons of workpieces, performing hot plastic forming on aluminum alloy blanks. This results in a dense internal structure free of macroscopic defects, with a specified ductile strength generally exceeding 250 MPa (compared to approximately 200 MPa for cast wheels). Forged aluminum alloy wheels have lower silicon content, fewer impurity elements, and a relatively higher density, making them superior to cast aluminum alloy wheels in both electrical and thermal conductivity. Furthermore, their excellent thermal conductivity helps reduce the risk of tire blowouts and minimize brake fade.

[0003] Against the backdrop of deepening vehicle system integration and multi-dimensional performance synergistic upgrade, new energy vehicles have put forward three core engineering and technical requirements for wheel hub products: (1) Lightweight requirements. As a key load-bearing component of unsprung mass, the reduction of wheel hub mass can directly improve the transient response characteristics of the vehicle, reduce the power consumption of the drive system, and shorten the braking distance, which has a systematic impact on the energy efficiency and handling quality of the vehicle; (2) High strength and high durability requirements. On the one hand, the large-scale application of low aspect ratio tires has enhanced lateral stiffness and steering response accuracy, but it has also significantly increased the local contact stress and bending stress in the rear flange area of ​​the wheel hub; on the other hand, due to the general increase in vehicle curb weight, the zero-speed peak torque output characteristics of the drive motor (peak torque is reached at zero speed), the increase in lateral load under high-speed cornering conditions, and the high-frequency alternating reverse torque caused by the braking energy recovery system, the wheel hub mounting plate and rear flange area face more severe stress concentration and fatigue damage risks, thus putting forward higher comprehensive requirements for its static strength, structural stiffness, impact toughness and long-cycle fatigue life; (3) Low carbonization requirements. This requirement extends beyond a single manufacturing stage, encompassing systemic dimensions such as material systems (e.g., composition control and impurity limit management of high-purity recycled aluminum alloys), process pathways (e.g., short-process, low-carbon processes like hot forging-cold spinning composite forming), energy structure (100% green electricity supply), and quantitative assessment of the carbon footprint throughout the entire lifecycle. Research indicates that using 100% green electricity to drive production and 70% recycled aluminum as raw material can reduce carbon emissions per unit of wheel hub by approximately 68%–72% compared to traditional processes. Aluminum possesses excellent closed-loop recycling capabilities; the energy consumption of the recycled aluminum smelting process is only about 5% of that of primary electrolytic aluminum, resulting in a simultaneous reduction of over 90% in carbon emission intensity.

[0004] Al-Mg-Si (6-series) aluminum alloys possess excellent forging properties, age-hardening responsiveness, corrosion resistance, weldability, and surface treatment compatibility, making them one of the most widely used alloy systems in lightweight automotive forgings. A key path to achieving sustainable development goals lies in constructing a "high-performance-low-carbon" collaborative design paradigm: that is, through chemical composition optimization, microstructure control, topology optimization design, and advanced forging processes, to systematically increase the application ratio and engineering adaptability of recycled aluminum materials while ensuring that wheel hubs meet functional safety, structural integrity, and reliability under all operating conditions. With the advancement of dual-carbon goals, using recycled aluminum to replace virgin aluminum in the production of aluminum alloy materials can reduce production energy consumption and carbon emissions by more than 90%, which is an inevitable trend in industry development. However, recycled aluminum raw materials (waste aluminum cans, 6-series scrap profiles, die-casting waste, etc.) usually contain high levels of Fe impurities. In 6-series aluminum alloys, Fe easily forms brittle β-AlFeSi phases in the form of needles and plates, which severely rupture the matrix and become the source of crack initiation and propagation. This significantly reduces the material's plasticity, toughness, and fatigue performance, failing to meet the requirements for load-bearing forgings. Currently, the mainstream industry solution is to remove iron through melt purification and dilution, but this significantly increases production costs and reduces the utilization rate of recycled aluminum. Some technologies modify the iron-rich phase by adding Mn and Cr elements, but the modification effect is limited, only converting the needle-like phase into micron-sized blocky phases, failing to achieve a strengthening effect. Furthermore, the composition is not precisely matched for different Fe contents, and performance still deteriorates significantly under high Fe conditions.

[0005] Among the existing publicly available technologies, some schemes have attempted to introduce rare earth elements into forged aluminum alloys to improve the morphology of the iron-rich phase. However, most of them use primary aluminum ingots as the main raw material, which has a low tolerance for Fe impurities and cannot be adapted to the low-carbon production route of high proportion of recycled aluminum. There are also some technologies for preparing aluminum alloys from recycled aluminum, but most of them belong to casting and die-casting alloy systems with high silicon content, which are not suitable for 6-series wrought components. Some research on forged aluminum alloys focuses on forging process and recrystallization structure control, but has not constructed a composition system for Mn-Cr-RE-Ni synergistic modification of the iron-rich phase. In summary, existing technologies either strictly limit the Fe content, making them unsuitable for high-proportion recycled aluminum feed, or they can only achieve micron-level improvement in the morphology of the iron-rich phase, failing to achieve nanoscale dispersion strengthening. They have not yet resolved the core contradiction between the high Fe impurities resulting from high-proportion recycled aluminum feed and the high strength and toughness requirements of forged aluminum alloys. They are unable to convert the harmful iron-rich phase into a nanoscale dispersion strengthening phase through precise compositional control under conditions of more than 50% recycled aluminum feed and a maximum Fe content of 0.40%, thus failing to achieve a balance between low carbon properties and high performance. Summary of the Invention

[0006] The purpose of this invention is to address the shortcomings of existing technologies by providing a low-carbon, high-performance Al-Mg-Si-RE aluminum alloy for forging and its preparation method. This invention breaks through the traditional approach of iron removal and impurity reduction. By matching the Fe content with the proportions of multiple microalloying elements (Mn / Cr / La / Ce / Ni / Ti), the Fe impurities introduced by recycled aluminum are transformed into nanoscale spherical dispersed strengthening phases. Under the low-carbon premise of using over 50% recycled aluminum as feedstock, high strength and high toughness performance of the forged aluminum alloy are achieved. The process can be directly adapted to existing industrial equipment and is easily scaled up. In terms of manufacturing process, this invention integrates key technologies such as high-proportion recycled aluminum (≥50%) melting and casting, multi-stage melt purification (including powder spraying refining, argon rotary blowing degassing, online degassing, and dual-stage filtration using ceramic filter plates and tubular filters), gradient homogenization heat treatment (540℃~560℃) / (10h~12h), precision forging temperature control (final forging temperature 380℃~420℃, average temperature drop rate ≤5℃ / s), and T6 aging treatment (solution treatment (530℃~540℃)×(4h~6h), aging treatment (170℃~190℃)×(4h~8h)). Through precise coupling of composition design and process parameters, the room temperature tensile strength of the obtained forgings is improved. R m ≥350MPa, specified plastic elongation strength R p0.2 ≥315MPa, elongation after fracture A ≥12%.

[0007] This invention provides a low-carbon, high-performance Al-Mg-Si-RE aluminum alloy for forging. The chemical composition, by mass fraction, includes: Si: 0.60%–0.90%, Mg: 0.90%–1.20%, Cu: 0.15%–0.30%, Fe: 0.12%–0.40%, Mn: 0.05%–0.25%, Cr: 0.15%–0.30%, La: 0.02%–0.10%, Ce: 0.02%–0.10%, Ni: 0.003%–0.05%, Ti: 0.03%–0.10%, with the balance being Al and unavoidable trace impurities.

[0008] The following proportioning constraints must be met simultaneously: The mass ratio of Mg to Si (Mg / Si) is 1.25 to 1.50 to ensure sufficient formation of the Mg2Si age-strengthening phase and avoid excess Mg or Si which would deteriorate plasticity.

[0009] Precise control is achieved by dividing the Fe content into two levels: When the Fe content is 0.12% to 0.30% (low Fe range), the mass ratio of Fe to (Mn+Cr) is 0.31 to 0.60, and the total mass fraction of La, Ce, Ni, and Ti is 0.08% to 0.12%. When the Fe content is greater than 0.30% and not greater than 0.40% (high Fe range), the mass ratio of Fe to (Mn+Cr) is 0.70 to 1.05, and the total mass fraction of La, Ce, Ni and Ti is 0.13% to 0.18%.

[0010] Furthermore, by mass fraction, Si is 0.65%–0.85%, Mg is 0.95%–1.15%, and Cu is 0.18%–0.28%. Within this more favorable composition range, the precipitation density of the Mg2Si strengthening phase and the solid solution strengthening effect of Cu achieve a better balance, while avoiding the damage to plasticity caused by the segregation of excess elements at grain boundaries.

[0011] Furthermore, when the Fe content is 0.12%–0.30% (low Fe range), the preferred mass ratio of Fe to (Mn+Cr) is 0.34–0.60, and the total mass fraction of La, Ce, Ni, and Ti is 0.09%–0.12%. When the Fe content is greater than 0.30% but not greater than 0.40% (high Fe range), the preferred mass ratio of Fe to (Mn+Cr) is 0.71–1.04, and the total mass fraction of La, Ce, Ni, and Ti is 0.14%–0.18%. Within the above-mentioned preferred parameter range, the spheroidization rate and dispersion uniformity of the iron-rich phase reach the optimal level.

[0012] Furthermore, among the unavoidable trace impurities, the mass fraction of a single impurity element is ≤0.05%, and the total mass fraction of all impurity elements is ≤0.15%, to ensure the purity of the alloy matrix and the consistency of metallurgical quality.

[0013] Furthermore, the rare earth element RE includes lanthanum (La) and cerium (Ce), wherein La and Ce are added in the form of Al-La and Al-Ce master alloys, respectively; and nickel (Ni) is introduced through an Al-Ni master alloy.

[0014] The above-mentioned synergistic regulation of components aims to precisely control the precipitation kinetics of the second phase, effectively suppress the abnormal coarsening of iron-rich phases such as α-Al(Fe / Mn)Si, thereby forming a diffusely distributed nanoscale iron-rich phase. This type of precipitated phase not only provides a significant dispersion strengthening effect, but also suppresses the precipitation of harmful iron-rich phases such as needle-like or blocky phases, thereby improving the overall strength and toughness of the material.

[0015] The method for determining the spheroidization rate of iron-rich phase particles in this invention includes microstructure analysis and quantitative statistical evaluation. The average ratio of the projected area of ​​each particle to the area of ​​its smallest circumscribed circle is used as the spheroidization rate. The sample is subjected to scanning electron microscopy (SEM) and TEM to acquire images of no less than 20 fields of view. Professional image analysis software is used to automatically identify particles and calculate morphological parameters. The number of effective particles is no less than 100.

[0016] The working principles of each element are as follows: Mg and Si, as fundamental strengthening elements, co-precipitate dispersed, fine, and thermally stable Mg2Si strengthening phases during solution treatment and aging. These phases are the core strengthening contributors to improving the alloy's specified ductile elongation strength and tensile strength. Strict control of the Mg / Si ratio can maximize the precipitation efficiency of the strengthening phase while avoiding the damage to plasticity caused by excess Si or Mg grain boundary segregation. Among them, Si has a dual function of strengthening phase formation and impurity phase regulation: with the synergistic effect of elements such as Mn and Cr, an appropriate amount of Si can regulate the thermodynamic stability and precipitation kinetics of Fe-based impurity phases, significantly reduce the interfacial energy of the β-AlFeSi phase, and promote the preferential nucleation and growth of the thermodynamically more stable α-Al(Fe / Mn)Si phase. If the Mg / Si mass ratio deviates from the preset design range, the precipitation kinetics of the Mg2Si phase will be unbalanced: when the ratio is too low, the amount of precipitated phase is insufficient and the dispersion decreases; when the ratio is too high, coarse Mg2Si phase and silicon-rich eutectic phase will precipitate along the grain boundaries, resulting in a decrease in tensile strength and specified plastic elongation strength, while significantly worsening the elongation after fracture. The impurity phase regulation effect of Si element mentioned above drives the transformation of the iron-rich phase into a spheroidized α-Al(Fe / Mn)Si phase with an average particle size of 100nm to 200nm, achieving a significant improvement in elongation after fracture while maintaining high strength and high iron content. A And fracture toughness.

[0017] Cu: Its strength primarily relies on the solid solution-aging strengthening mechanism. The metastable phases such as θ′ (Al₂Cu) precipitated during aging significantly enhance the alloy's strength. Furthermore, trace amounts of Cu can interact with Mg and Si, promoting the precipitation of multi-component composite strengthening phases such as Q′ (Al₅Mg₈Cu₂Si₆), further improving the alloy's peak strength, thermal stability, and resistance to natural aging softening. In this system, the Cu content is set at 0.15%–0.30%. While ensuring sufficient precipitation of the θ′ phase, the precipitation of the primary Al₂Cu phase (with a melting point of approximately 548℃, which easily precipitates along grain boundaries at the end of ingot solidification and induces thermal cracking) is strictly avoided, thereby achieving a comprehensive and synergistic improvement in strength, plasticity, and hot working properties.

[0018] Fe: Primarily introduced from recycled aluminum raw materials. This invention does not aim to completely remove Fe, but rather transforms it into a beneficial dispersed strengthening phase through multi-element synergistic modification. When the Fe content is below 0.12%, the dispersion strengthening effect is insufficient; when it is above 0.40%, coarse and brittle phases are easily generated, making effective modification impossible. When the Fe content exceeds 0.4%, the nucleation driving force of the β-AlFeSi phase is significantly enhanced, and the volume fraction of needle-like and blocky iron-rich phases between ingot dendrites increases, increasing the susceptibility to hot cracking. These phases are prone to elongation along the deformation direction during subsequent hot working, becoming core sites for stress concentration and microcrack initiation.

[0019] Mn and Cr synergistically promote the transformation of the acicular β-AlFeSi phase to the equiaxed α-Al(Fe / Mn / Cr)Si phase, effectively inhibiting the coarsening, network connectivity, and grain boundary segregation of the brittle iron-rich phase. The ratio of Mn and Cr must be matched with the Fe content; insufficient Mn will result in inadequate modification, while excessive Mn will easily form coarse intermetallic compounds that impair toughness. Mn can promote the transformation of the β-AlFeSi phase to the equiaxed α-Al(Fe / Mn)Si phase, significantly reducing the aspect ratio of the iron-rich phase from >10:1 to ≤3:1. Cr inhibits the segregation behavior of Fe atoms at grain boundaries and subgrain boundaries, regulates interfacial diffusion kinetics, and effectively inhibits the formation of a continuous network Fe matrix phase.

[0020] La, Ce (rare earth RE), Ni, and Ti: A quaternary synergy achieves thermodynamic stability control of high-temperature precipitates, enhanced grain boundary pinning effect, and spheroidization reconstruction of Fe-based precipitates. By regulating the interfacial energy and growth kinetics of the iron-rich phase, it breaks down continuous brittle phases and refines them from micron-sized needle / block or lamellar structures into isolated, near-spherical, uniformly sized dispersed nanoparticles of 100nm–200nm. These precipitates exhibit both excellent high-temperature stability and high-density dispersion. Ti is introduced in the form of an Al-Ti-B master alloy to refine grains and improve the uniformity of the ingot microstructure. The effect of trace amounts of Ni on the alloy breaks through the single effect of traditional solid solution strengthening and interfacial segregation, possessing the ability to synergistically control the alloy solidification path, recrystallization kinetics, and high-temperature microstructure stability across scales. Specifically, the spheroidization rate of the iron-rich phase is increased from less than 20% to ≥85%, and the average diameter of the spheroidized particles is controlled within the range of 100nm–200nm. This microstructure transformation significantly alleviates stress concentration and effectively inhibits crack initiation and propagation, enabling the alloy to achieve room temperature tensile elongation after fracture even under high Fe content (Fe≥0.2%). A The content of rare earth elements (La, Ce, Ni, and Ti) should be ≥10%, which simultaneously improves the crack resistance during hot forging. However, when the total addition of La, Ce, Ni, and Ti exceeds the design limit, on the one hand, it is easy to form coarse Al3(RE) or Al3Ti primary clusters, which significantly reduces melt fluidity and worsens the rheological behavior of hot forging; on the other hand, excessive rare earth elements will excessively inhibit dynamic recrystallization nucleation at grain boundaries, resulting in a significant bimodal distribution of grain size (fine-grained region and coarse-grained region) in the forged microstructure. On the other hand, if the total addition of La, Ce, Ni, and Ti is too low, it will weaken the interfacial energy regulation ability of the α-Al(Fe / Mn)Si phase, reduce the spheroidization rate of the iron-rich phase, and thus cause room temperature elongation at break. A The overall positive effect is reduced. It should be noted that the above-mentioned comprehensive positive effect reaches the optimal balance when the Ni addition amount does not exceed 0.05%; exceeding this threshold can easily induce the local aggregation of coarse rare earth enriched phases, which in turn leads to the deterioration of plasticity and fatigue performance.

[0021] If the contents of the eight trace elements Fe, Mn, Cr, Si, La, Ce, Ni, and Ti in this invention, and their mass ratios or molar ratios, deviate from the preset design range, it will systematically interfere with the selective precipitation behavior of the primary phase, the solid-state phase transformation path, and the multiphase competitive precipitation kinetics during the alloy solidification process, thereby significantly weakening its microstructure thermal stability and mechanical property retention under service conditions. Specifically: when the Fe content exceeds 0.4%, the nucleation driving force of the β-AlFeSi phase is significantly enhanced, leading to an increase in the volume fraction of needle-like and blocky iron-rich phases in the interdendritic space of the ingot. This not only increases the susceptibility to hot cracking, but also, because this phase is prone to elongation along the deformation direction during subsequent hot working, it becomes the core site for stress concentration and microcrack initiation. If the Si content is too low or the Cu content is too high, and the Mg / Si ratio deviates from the specified range, the precipitation density of the Mg2Si strengthening phase decreases or the coarsening of the Al2Cu phase intensifies, resulting in a decrease in peak aging tensile strength or elongation after fracture. A Insufficient; and when the total addition of La, Ce, Ni and Ti deviates from the design range, it will also weaken the spheroidization and reconstruction effect of the iron-rich phase or induce the aggregation of coarse rare earth phases, as described above.

[0022] Furthermore, the aluminum alloy is smelted from a furnace charge containing a basic aluminum source and recycled aluminum, with the recycled aluminum accounting for ≥50% of the total mass of the furnace charge. The basic aluminum source is electrolytic aluminum liquid or high-purity aluminum ingot, which serves as an impurity dilution medium and has the triple functions of stabilizing the main components, reducing the Fe / Si impurity concentration, and improving the purity of the melt. Its addition ratio is calculated based on the measured Fe and Si content of the incoming raw materials for mass balance and is dynamically adjusted. The recycled aluminum includes at least two of the following: waste aluminum cans, 6-series waste profiles, and ADC12 die-casting waste. Among them, waste aluminum cans are Fe and Mn enriched recycled aluminum sources, 6-series waste profiles are Mg and Si synergistic supplementary sources, and ADC12 die-casting waste has both Cu and Si supplementary functions. Among them, waste aluminum can recycling material comes from aluminum beverage cans, food cans or their crushed material recycled after consumption; ADC12 die casting waste refers to the die casting housing of scrapped automobile or motorcycle engines; 6 series industrial waste profiles cover automobile body waste profiles, start and end materials, cutting materials, scrap materials, scrap profiles and trial-produced unqualified profiles generated in the production process of aluminum profiles.

[0023] Furthermore, in the forged alloy treated with T6, the iron-rich phase consists of highly isolated, uniformly sized (100nm~200nm), nearly spherical (sphericity ≥85%) α-Al(Fe / Mn / Cr)Si particles that are three-dimensionally dispersed within the α-Al grains. The aspect ratio of the iron-rich phase is ≤3:1, and the network-connected iron-rich phase is effectively suppressed.

[0024] Furthermore, the forged alloy treated with T6 heat meets the following mechanical properties: Low Fe range (0.12%–0.30%): Tensile strengthR m ≥350MPa, specified plastic elongation strength R p0.2 ≥315MPa, elongation after fracture A ≥13%; High Fe range (greater than 0.30% and not greater than 0.40%): tensile strength R m ≥350MPa, specified plastic elongation strength R p0.2 ≥320MPa, elongation after fracture A ≥12%.

[0025] The preparation method of the above-mentioned low-carbon high-performance Al-Mg-Si-RE aluminum alloy for forging includes the following steps: Raw material pretreatment: Based on the morphological characteristics and contamination types of different types of recycled aluminum raw materials, graded sorting, surface cleaning (paint removal / degreasing / wiping) and geometric shape adaptation (crushing / shredding / blocking) are carried out to eliminate oil stains, coatings and inclusions on the surface of recycled materials and ensure the purity of the melt.

[0026] Specifically, waste aluminum cans are sorted and removed of foreign objects through a combination of manual and mechanical methods, and then successively crushed, magnetically separated to remove iron, stripped of organic coatings, alkaline degreasing and cleaning, hot air circulating drying, and hydraulic briquetting; ADC12 die-casting waste undergoes alkaline degreasing, crushing, magnetic separation to remove iron, and hot air drying; 6-series waste aluminum profiles are sorted, shredded to reduce volume, magnetically separated to remove iron, and undergo multi-stage cleaning (including alkaline degreasing and mechanical scrubbing to remove dirt).

[0027] Melting and Refining: First, the basic aluminum source (electrolytic aluminum liquid / high-purity aluminum ingot) and some recycled aluminum raw materials (such as 6-series scrap profiles or ADC12 die-casting waste) are melted to form an initial molten pool. Then, preheated and briquetted lightweight recycled aluminum materials such as waste aluminum cans are slowly pressed into the molten pool in batches to reduce drastic temperature fluctuations, lower the risk of oxide inclusions, and promote full melting and homogenization of the materials. Electromagnetic stirring (frequency 20Hz~30Hz, time 15min~20min) is performed to ensure melt homogeneity. After spectral analysis, Al-Mn, Al-Cr, and other additives are added. The composition was adjusted using intermediate alloys such as Al-Cu, Al-Si, Al-La, Al-Ce, and Al-Ni, and finally pure magnesium was added. Subsequently, multi-stage purification was carried out using powdered granular refining agent (refining for 15-20 minutes) + high-purity argon rotary blowing degassing (10-15 minutes), with the refining temperature controlled at 730℃-750℃. After slag removal and standing for 30-40 minutes, qualified aluminum melt with uniform composition and meeting the purity standards was obtained. Before casting, Al-Ti-B intermediate alloy was added online in the casting tank to refine the grains.

[0028] Vertical semi-continuous casting: After the melt is degassed online with argon in a sealed box and then filtered through a ceramic filter plate and a tubular filter, a round ingot for forging is prepared at a casting temperature of 720℃~740℃ and a casting speed of (75~100) mm / min. The casting speed is dynamically matched according to the ingot diameter and cooling conditions to ensure uniform solidified shell thickness and appropriate liquid cavity depth, and to suppress defects such as central shrinkage porosity, grain coarsening and surface cold shut.

[0029] Three-stage homogenization treatment: The round ingot is subjected to three-stage homogenization treatment to fully dissolve the non-equilibrium eutectic phase and promote the diffusion and redistribution of solute atoms, thereby effectively eliminating dendritic segregation and improving the uniformity of microstructure and properties, while inhibiting the precipitation and aggregation of coarse iron-rich phases (Al3Fe, Al6Fe); Specifically: the temperature is gradually increased to 540℃~560℃ and held for 10 h~12 h; after the holding period, segmented controllable cooling is carried out, first cooling to 300℃ at a rate of (100~300)℃ / h, and then slowly cooling to below 150℃ with the furnace before unloading.

[0030] Three-step closed-die forging: The ingot is preheated at 430℃~470℃ for 1.5h~2.5h to achieve temperature field homogenization and reduce thermal stress gradient, ensuring the stability of the microstructure and rheological compatibility during the forging process. Subsequently, it undergoes three steps of closed-die forging: pre-forging, precision forging, and straightening. Pre-forging uses an 8000t~10000t forging press, precision forging uses a 4000t~6000t forging press, and straightening uses an 800t forging press. The average temperature drop rate during forging is ≤5℃ / s, and the fluctuation range of the local temperature drop rate is controlled within ±0.8℃ / s. The final forging temperature is controlled at 380℃~420℃. Precise temperature control during forging significantly inhibits microcrack initiation and ensures uniform internal microstructure of the forging.

[0031] T6 heat treatment: The forging is solution-treated at 530℃~540℃ for 4h~6h, then rapidly quenched, followed by single-stage aging at 170℃~190℃ for 4h~8h, and finally air-cooled to obtain the finished forging. This T6 heat treatment regime matches the kinetic stages of GP zone nucleation, orderly precipitation of metastable β″ phase, and sufficient growth of equilibrium β′ phase, achieving synergistic optimization of strength and plasticity while suppressing over-aging tendency.

[0032] The complete preparation process of this invention includes five key process strategies: ① Raw material end: Recycled aluminum raw materials undergo optical sorting, alkaline washing and paint removal, mechanical crushing, and magnetic separation-eddy current combined pretreatment, and are calibrated in a closed loop with the basic aluminum source and multi-element intermediate alloy, with the proportion of recycled aluminum feeding ≥50%; ② Melt purification: A four-stage joint control is implemented, including powder spraying refining, argon rotary blowing, online degassing, and ceramic + tubular filter deep filtration, to obtain a high-purity aluminum melt that meets the metallurgical purity requirements for forged round ingots; ③ Homogenization heat treatment: A gradient heating process is adopted to ensure sufficient solid solution of Fe, Mn, and Cr, and reduce the residue of coarse intermetallic compounds; ④ Precise temperature control is implemented in the forging process, with the final forging temperature controlled at 380℃~420℃, the average temperature drop rate ≤5℃ / s, and the fluctuation range of the local temperature drop rate controlled within ±0.8℃ / s, significantly inhibiting the initiation of microcracks and uneven microstructure; ⑤ T6 heat treatment is matched with aging precipitation kinetics to synergistically optimize strength and plasticity.

[0033] The Al-Mg-Si-RE aluminum alloy system constructed in this invention, with "precise window control of Fe content—multi-element synergistic phase transformation control—deep coupling of thermomechanical processes" as its core technology, achieves the following beneficial effects through the synergistic matching of composition design and preparation process: Low-carbon and environmentally friendly with high recycling rate: It can achieve a high proportion of recycled aluminum feeding of more than 50%, which significantly reduces energy consumption and carbon emissions in the production process. It can reduce the carbon emissions of a unit product throughout its entire life cycle by about 30% compared with the traditional primary aluminum benchmark process, which meets the development needs of the low-carbon supply chain of new energy vehicles and has significant environmental and economic benefits.

[0034] Impurity Resource Utilization, Turning Waste into Treasure: Breaking through the traditional technical path of iron removal and impurity reduction, by precisely controlling the multi-element ratio in stages, harmful Fe impurities brought in by recycled aluminum are transformed into spherical dispersed strengthening phases of 100nm to 200nm, realizing the resource utilization of impurities. Under high Fe conditions, even better dispersion strengthening effect is obtained. This provides a structured design paradigm with a clear composition-microstructure-macro performance mapping relationship for the development of high-performance aluminum alloy materials for the circular economy.

[0035] Strength and toughness combined, excellent performance: T6 forgings possess both high strength and high plasticity, with specified plastic elongation strength. R p0.2 The maximum strength can reach over 320 MPa, and the elongation after fracture is... A Maintaining a concentration above 12% ensures that the performance requirements of critical load-bearing components such as automotive wheel hubs and suspension control arms, which withstand alternating impact loads, are met. This composition system guarantees high strength ( R m ≥350MPa R p0.2 ≥315MPa), high plasticity ( AWhile achieving ≥12% and designable thermal stability, it enables the directional conversion of inherent impurities in recycled aluminum raw materials, thereby obtaining additional performance gains.

[0036] The technology is mature and easy to implement: the entire preparation process can be achieved based on existing industrial smelting, semi-continuous casting, forging and heat treatment equipment, without the need for new special equipment. The process parameters are highly controllable, the product performance is highly stable, and it is easy to promote and scale up production. Attached Figure Description

[0037] Figure 1 Metallographic images of the Al-Mg-Si-RE aluminum alloy forging (T6 treatment) prepared in Example 2; Figure 2 The images show the HAADF-STEM high-resolution images of the iron-rich phase and the EDS distribution diagrams of Fe, Mn, Cr, and Si elements in the Al-Mg-Si-RE aluminum alloy forging (T6 treatment) prepared in Example 2. Figure 3 High-resolution HAADF-STEM images of the iron-rich phase and EDS distribution maps of Fe, Mn, Cr, and Si elements in the Al-Mg-Si-RE aluminum alloy forging (T6 treatment) prepared in Comparative Example 3. Figure 4 High-resolution HAADF-STEM images of the iron-rich phase and EDS distribution maps of Fe, La, Ce, Ni, and Ti elements in the Al-Mg-Si-RE aluminum alloy forging (T6 treatment) prepared in Comparative Example 6. Detailed Implementation

[0038] The present invention will be further described below with reference to specific embodiments. It should be noted that the scope of protection of the present invention is not limited to the listed embodiments; without departing from the core concept and technical essence of the present invention, those skilled in the art can systematically adapt and engineer the aluminum raw materials, the types and proportions of intermediate alloy additives, the smelting purification process (degassing, filtration, online refining), the homogenization heat treatment regime, the forging forming strategy, and the T6 heat treatment process parameters (solution temperature and time, aging temperature and time) based on the compositional characteristics of recycled aluminum raw materials (such as Fe, Si, Cu content and impurity spectrum), the type of smelting equipment, the forming process path, the hot working parameters (forging temperature range, strain rate, deformation amount), and the end-service requirements (strength-plasticity matching, fatigue life, corrosion resistance). These all fall within the scope of protection of the present invention.

[0039] The aluminum alloy of this invention can be prepared entirely from virgin aluminum raw materials, or it can be prepared using recycled aluminum accounting for ≥50% of the total furnace charge to achieve low-carbon production. In some embodiments, the proportion of recycled aluminum is less than 50%, and these embodiments are mainly used to verify the effect of the alloy composition itself on the control of material properties. Unless otherwise explicitly stated, all chemical components in the following embodiments and comparative examples are expressed as a percentage by mass, with the balance being Al and unavoidable trace impurities; the proportions of waste aluminum cans, industrial waste profiles, and ADC12 die-cast waste parts are all expressed as a percentage of the total furnace charge mass.

[0040] The Al-Mg-Si-RE aluminum alloy prepared by this invention was subjected to mechanical property testing in accordance with national standards. The forging tensile specimens were cylindrical rod-shaped specimens with a diameter of 6 mm and a gauge length of 30 mm. The arithmetic mean of three sets of valid test data was taken for each mechanical property index.

[0041] Table 1 lists the target chemical composition of the Al-Mg-Si-RE aluminum alloys in the examples and comparative examples.

[0042] Table 1. Target chemical composition of the examples and comparative examples (unit: wt.%)

[0043] Example 1 A low-carbon, high-performance Al-Mg-Si-RE aluminum alloy for forging, comprising, by mass percentage: 0.12% Fe, 0.10% Mn, 0.25% Cr, 0.75% Si, 1.05% Mg, 0.25% Cu, 0.02% La, 0.02% Ce, 0.006% Ni, and 0.05% Ti, with the balance being Al and unavoidable trace impurities. The Mg / Si mass ratio is 1.40, the Fe / (Mn+Cr) mass ratio is 0.34, and the sum of the mass percentages of La, Ce, Ni, and Ti is 0.096.

[0044] The raw materials used in the preparation are as follows: pure aluminum ingot (910 kg, accounting for 90%), Al-20Mn master alloy (5.1 kg), Al-10Cr master alloy (25.3 kg), Al-10La master alloy (2.1 kg), Al-10Ce master alloy (2.1 kg), Al-10Ni master alloy (0.61 kg), Al-5Ti-1B master alloy (10.5 kg), pure magnesium ingot (10.9 kg), Al-20Si master alloy (38 kg) and Al-50Cu master alloy (5.1 kg). Ultimately, the actual chemical composition, by mass percentage, is 0.125% Fe, 0.101% Mn, 0.25% Cr, 0.752% Si, 1.06% Mg, 0.252% Cu, 0.02% La, 0.021% Ce, 0.006% Ni, and 0.052% Ti, with the balance being Al and unavoidable trace inclusions.

[0045] The preparation process is carried out according to the following steps: (1) Melting and refining: Accurately weigh pure aluminum ingots, Al-20Mn, Al-10Cr, Al-50Cu, Al-20Si, Al-10La, Al-10Ce, and Al-10Ni master alloys and pure magnesium ingots according to the target composition, and put them into the melting furnace. After melting at 720℃~760℃, electromagnetic stirring is performed (frequency 20Hz~30Hz, time 15min~20min); the melt is analyzed by spectral analysis and dynamically controlled to ensure that Mg, Si, Cu, The contents of Fe, Mn, Cr, La, Ce, and Ni meet the requirements; then, multi-stage composite refining is carried out at 730℃~750℃, including refining with powdered granular refining agent for 15min~20min and high-purity argon rotary blowing degassing (10min~15min), followed by efficient slag removal and standing for 30min~40min to obtain qualified aluminum melt with uniform composition and qualified purity; finally, Al-Ti-B master alloy is added online in the flow channel to make the Ti content reach the target range.

[0046] (2) Degassing-Filtration-Casting: A closed degassing box is used, and high-purity argon gas is introduced to implement online rotary degassing; the melt flows through a ceramic online filter and a tubular filter in sequence for deep filtration, simultaneously removing oxide inclusions and micron-sized particles; then, a vertical semi-continuous casting process is used to prepare high-quality aluminum alloy round ingots that meet the requirements of forging. The key casting parameters are controlled as follows: the casting temperature is 720℃~740℃, the casting speed is 75mm / min~100mm / min, and the process parameters are dynamically adjusted according to the ingot diameter and cooling intensity to ensure uniform solidified shell thickness and appropriate liquid cavity depth, effectively suppressing typical casting defects such as central shrinkage porosity, grain coarsening and surface cold shut.

[0047] (3) Homogenization-Forging-Heat Treatment: The homogenization treatment of the ingot is carried out at 540℃~560℃, and the holding time is controlled at 10h~12h. After the holding time, segmented controlled cooling is implemented: first, it is cooled to 300℃ at a rate of 100℃ / h~300℃ / h, and then slowly cooled to below 150℃ in the furnace before being taken out. The homogenized ingot must be preheated before forging. The preheating temperature is controlled in the range of 430℃~470℃ and held for 1.5h~2.5h. The forging process adopts precise temperature control. The final forging temperature is controlled in the range of 380℃~420℃, the average temperature drop rate is ≤5℃ / s, and the fluctuation range of the local temperature drop rate is controlled within ±0.8℃ / s, which effectively inhibits the initiation of microcracks and the inhomogeneity of the structure. The forging process employs closed-die forging and is implemented in three stages: the first stage involves pre-forging the billet using an 8000t forging machine; the second stage involves precision forging using a 4000t forging machine; and the third stage involves straightening and shaping using an 800t forging machine. The forgings undergo T6 heat treatment, including two key processes: solution treatment and aging strengthening. The solution treatment temperature is 540℃, the holding time is 6 hours, and the aging process is 180℃ for 6 hours.

[0048] The Al-Mg-Si-RE aluminum alloy final forging prepared in this embodiment, after T6 heat treatment, exhibits the following average tensile strength at room temperature. R m Up to 356 MPa, specified plastic elongation strength R p0.2 The strength is 318 MPa, and the elongation after fracture is... A The value is 14.3%; the above mechanical properties meet the technical requirements of new energy vehicle chassis structural components for strength and toughness matching and service reliability.

[0049] Example 2 A low-carbon, high-performance Al-Mg-Si-RE aluminum alloy for forging, comprising, by mass percentage: 0.25% Fe, 0.18% Mn, 0.25% Cr, 0.75% Si, 1.05% Mg, 0.25% Cu, 0.03% La, 0.03% Ce, 0.006% Ni, and 0.05% Ti, with the balance being Al and unavoidable trace impurities. The Mg / Si mass ratio is 1.40, the Fe / (Mn+Cr) mass ratio is 0.58, and the sum of the mass percentages of La, Ce, Ni, and Ti is 0.116.

[0050] This embodiment, based on the process of Embodiment 1, further introduces waste aluminum cans and scrap ADC12 castings. The raw material composition used in the preparation is as follows: 70 kg of aluminum cans without magnetic separation for iron removal, 60 kg of aluminum cans after magnetic separation for iron removal, 72 kg of scrap ADC12 castings, and recycled aluminum material accounting for 20% of the total mass of the metal furnace charge; the remaining components are pure aluminum ingots (750 kg, accounting for 74%), Al-20Mn master alloy (3.8 kg), Al-10Cr master alloy (24.8 kg), Al-10La master alloy (3.2 kg), Al-10Ce master alloy (3.1 kg), Al-10Ni master alloy (0.61 kg), Al-5Ti-1B master alloy (10.5 kg), pure magnesium ingots (9.4 kg), and Al-50Cu master alloy (2.7 kg). By introducing scrap ADC12 castings to replace Al-20Si master alloy and part of Al-50Cu master alloy, the raw material cost is effectively reduced. Ultimately, the actual chemical composition, by mass percentage, is 0.254% Fe, 0.182% Mn, 0.249% Cr, 0.748% Si, 1.05% Mg, 0.248% Cu, 0.03% La, 0.03% Ce, 0.006% Ni, and 0.052% Ti, with the balance being Al and unavoidable trace inclusions.

[0051] The preparation process is carried out according to the following steps: (1) Raw material pretreatment: For recycled aluminum raw materials such as waste aluminum cans and ADC12 die casting waste, according to their morphological characteristics and pollution type, graded sorting (removing non-aluminum foreign matter and high melting point inclusions), surface purification (including organic coating pyrolysis, alkaline degreasing and mechanical scrubbing) and geometric shape adaptation treatment (such as crushing, shredding and hydraulic pressing) are carried out to ensure the stability and composition controllability of the subsequent smelting process.

[0052] (2) Melting and refining: First, ADC12 waste castings and pure aluminum ingots are put into the melting furnace and the basic molten pool is established at 720℃~760℃. Then, the preheated and briquetted recycled cans are slowly pressed into the molten pool in batches and electromagnetically stirred (frequency 20Hz~30Hz, time 15min~20min). Then, according to the aluminum liquid composition test results, intermediate alloy and pure magnesium ingots are added in sequence to achieve the classification, precision and dynamic feeding of main elements and micro-alloying components. Then, multi-stage composite refining is carried out at 730℃~750℃, including powdered refining agent (using granular refining agent, time 15min~20min) and high-purity argon rotary blowing degassing (10min~15min). Then, the slag is efficiently removed and the mixture is allowed to stand for 30min~40min to obtain qualified aluminum melt with uniform composition and qualified purity. Finally, Al-Ti-B intermediate alloy is added online in the trough to make the Ti content reach the target range.

[0053] (3) Key process steps such as degassing, filtration, casting and homogenization, forging and heat treatment are all carried out in accordance with Example 1.

[0054] The Al-Mg-Si-RE aluminum alloy final forging prepared in this embodiment, after T6 heat treatment, exhibits the following average tensile strength at room temperature. R m Up to 360 MPa, specified plastic elongation strength R p0.2 The strength is 321 MPa, and the elongation after fracture is... A It is 13.8%.

[0055] Example 3 A low-carbon, high-performance Al-Mg-Si-RE aluminum alloy for forging differs from Example 2 in that the aluminum alloy comprises, by mass percentage: 0.30% Fe, 0.20% Mn, 0.30% Cr, 0.85% Si, 1.15% Mg, 0.25% Cu, 0.03% La, 0.03% Ce, 0.01% Ni, and 0.05% Ti, with the balance being Al and unavoidable trace impurities. The Mg / Si mass ratio is 1.35, the Fe / (Mn+Cr) mass ratio is 0.60, and the sum of the mass percentages of La, Ce, Ni, and Ti is 0.12.

[0056] This embodiment uses the same preparation method as Embodiment 2, but differs in the mass ratio of recycled aluminum to pure aluminum ingots, and the addition amounts of Fe (increased from 0.25% to 0.30%), Mn, Cr, Si, Mg, and Ni. The raw material composition is as follows: 105 kg of aluminum cans without magnetic separation for iron removal, 100 kg of aluminum cans after magnetic separation for iron removal, 74.5 kg of ADC12 waste castings, 120 kg of 6-series waste profiles, with recycled aluminum accounting for 40% of the total mass of the metal furnace charge. The remaining components are pure aluminum ingots (550 kg, accounting for 55%), Al-20Mn master alloy (1.6 kg), Al-10Cr master alloy (26.5 kg), Al-10La master alloy (3.2 kg), Al-10Ce master alloy (3.1 kg), Al-10Ni master alloy (1.05 kg), Al-5Ti-1B master alloy (7.7 kg), pure magnesium ingots (8.4 kg), and Al-50Cu master alloy (2.1 kg). The final chemical composition, by mass percentage, is 0.30% Fe, 0.203% Mn, 0.298% Cr, 0.851% Si, 1.15% Mg, 0.248% Cu, 0.03% La, 0.03% Ce, 0.01% Ni, and 0.05% Ti, with the balance being Al and unavoidable trace inclusions.

[0057] The Al-Mg-Si-RE aluminum alloy final forging prepared in this embodiment, after T6 heat treatment, exhibits the following average tensile strength at room temperature. R m Up to 367 MPa, specified plastic elongation strength R p0.2 The strength is 329 MPa, and the elongation after fracture is... A It is 13.0%.

[0058] Example 4 A low-carbon, high-performance Al-Mg-Si-RE aluminum alloy for forging differs from Example 2 in that the aluminum alloy comprises, by mass percentage: 0.35% Fe, 0.20% Mn, 0.25% Cr, 0.75% Si, 1.12% Mg, 0.25% Cu, 0.04% La, 0.04% Ce, 0.01% Ni, and 0.05% Ti, with the balance being Al and unavoidable trace impurities. The Mg / Si mass ratio is 1.493, the Fe / (Mn+Cr) mass ratio is 0.778, and the sum of the mass percentages of La, Ce, Ni, and Ti is 0.14.

[0059] This embodiment uses the same preparation method as Embodiment 2, but differs in the mass ratio of recycled aluminum to pure aluminum ingots, and the amount of Fe (increased from 0.25% to 0.35%), Mn, Mg, La, Ce, and Ni added. The raw materials used in the preparation are as follows: 250 kg of non-magnetically separated iron-removed beverage cans, 60 kg of ADC12 waste castings, 200 kg of 6-series waste profiles, and recycled aluminum material accounts for 51% of the total mass of the metal furnace charge; the remaining components are pure aluminum ingots (450 kg, accounting for 45%), Al-10Cr master alloy (20 kg), Al-10La master alloy (4.3 kg), Al-10Ce master alloy (4.2 kg), Al-10Ni master alloy (1.05 kg), Al-5Ti-1B master alloy (6.1 kg), pure magnesium ingots (6.83 kg), and Al-50Cu master alloy (2.2 kg). Ultimately, the actual chemical composition, by mass percentage, is 0.35% Fe, 0.208% Mn, 0.252% Cr, 0.748% Si, 1.121% Mg, 0.255% Cu, 0.042% La, 0.039% Ce, 0.01% Ni, and 0.05% Ti, with the balance being Al and unavoidable trace inclusions.

[0060] The Al-Mg-Si-RE aluminum alloy final forging prepared in this embodiment, after T6 heat treatment, exhibits the following average tensile strength at room temperature. R m Up to 355 MPa, specified plastic elongation strength R p0.2The strength is 324 MPa, and the elongation after fracture is... A It is 12.5%.

[0061] Example 5 A low-carbon, high-performance Al-Mg-Si-RE aluminum alloy for forging differs from Example 2 in that the aluminum alloy comprises, by mass percentage: 0.35% Fe, 0.25% Mn, 0.24% Cr, 0.75% Si, 1.05% Mg, 0.20% Cu, 0.03% La, 0.04% Ce, 0.02% Ni, and 0.06% Ti, with the balance being Al and unavoidable trace impurities. The Mg / Si mass ratio is 1.40, the Fe / (Mn+Cr) mass ratio is 0.714, and the sum of the mass percentages of La, Ce, Ni, and Ti is 0.15.

[0062] This embodiment uses the same preparation method as Embodiment 2, but differs in the mass ratio of recycled aluminum to pure aluminum ingots, and the amount of Fe (increased from 0.25% to 0.35%), Mn, Cr, Cu, Ce, Ni, and Ti added. The raw material composition used in the preparation is as follows: 330 kg of non-magnetically separated iron-removed beverage cans, 200 kg of 6-series waste profiles, and recycled aluminum material accounts for 52% of the total mass of metal furnace charge; the remaining components are pure aluminum ingots (410 kg, accounting for 40%), Al-10Cr master alloy (19.5 kg), Al-10La master alloy (3.3 kg), Al-10Ce master alloy (3.1 kg), Al-10Ni master alloy (2 kg), Al-5Ti-1B master alloy (6.1 kg), pure magnesium ingots (5.5 kg), and Al-50Cu master alloy (3.1 kg). Ultimately, the actual chemical composition, by mass percentage, is 0.352% Fe, 0.247% Mn, 0.241% Cr, 0.749% Si, 1.053% Mg, 0.202% Cu, 0.031% La, 0.031% Ce, 0.02% Ni, and 0.05% Ti, with the balance being Al and unavoidable trace inclusions.

[0063] The Al-Mg-Si-RE aluminum alloy final forging prepared in this embodiment, after T6 heat treatment, exhibits the following average tensile strength at room temperature. R m Up to 351 MPa, specified plastic elongation strength R p0.2 The strength is 321 MPa, and the elongation after fracture is... A It is 12.4%.

[0064] Example 6 A low-carbon, high-performance Al-Mg-Si-RE aluminum alloy for forging differs from Example 2 in that the aluminum alloy comprises, by mass percentage: 0.40% Fe, 0.20% Mn, 0.30% Cr, 0.84% ​​Si, 1.05% Mg, 0.25% Cu, 0.05% La, 0.05% Ce, 0.01% Ni, and 0.07% Ti, with the balance being Al and unavoidable trace impurities. The Mg / Si mass ratio is 1.25, the Fe / (Mn+Cr) mass ratio is 0.80, and the sum of the mass percentages of La, Ce, Ni, and Ti is 0.18.

[0065] This embodiment uses the same preparation method as Embodiment 2, but differs in the mass ratio of recycled aluminum to pure aluminum ingots, and the amount of Fe (increased from 0.25% to 0.4%), Mn, Cr, La, Ce, Ni, and Ti added. The raw materials used in the preparation are as follows: 330 kg of non-magnetically separated iron-removed beverage cans, 70 kg of ADC12 waste castings, 200 kg of 6-series waste profiles, and recycled aluminum material accounts for 57% of the total mass of the metal furnace charge; the remaining components are pure aluminum ingots (400 kg, accounting for 38%), Al-10Cr master alloy (21 kg), Al-10La master alloy (5.8 kg), Al-10Ce master alloy (5.3 kg), Al-10Ni master alloy (1.1 kg), Al-5Ti-1B master alloy (10.8 kg), pure magnesium ingots (5.9 kg), and Al-50Cu master alloy (2 kg). Ultimately, the actual chemical composition, by mass percentage, is 0.40% Fe, 0.205% Mn, 0.296% Cr, 0.84% ​​Si, 1.056% Mg, 0.249% Cu, 0.051% La, 0.05% Ce, 0.01% Ni, and 0.07% Ti, with the balance being Al and unavoidable trace inclusions.

[0066] The Al-Mg-Si-RE aluminum alloy final forging prepared in this embodiment, after T6 heat treatment, exhibits the following average tensile strength at room temperature. R m Up to 354 MPa, specified plastic elongation strength R p0.2 The strength is 322 MPa, and the elongation after fracture is... A It is 12.1%.

[0067] Example 7 A low-carbon, high-performance Al-Mg-Si-RE aluminum alloy for forging differs from Example 2 in that the aluminum alloy comprises, by mass percentage: 0.35% Fe, 0.184% Mn, 0.154% Cr, 0.82% Si, 1.05% Mg, 0.25% Cu, 0.03% La, 0.05% Ce, 0.01% Ni, and 0.05% Ti, with the balance being Al and unavoidable trace impurities. The Mg / Si mass ratio is 1.28, the Fe / (Mn+Cr) mass ratio is 1.036, and the sum of the mass percentages of La, Ce, Ni, and Ti is 0.14.

[0068] This embodiment uses the same preparation method as Embodiment 2, but there are differences in the mass ratio of recycled aluminum to pure aluminum ingots, and the amount of Fe (increased from 0.25% to 0.35%), Mn, Cr, Si, Ce and Ni elements added. The raw material composition used in the preparation is as follows: 245 kg of non-magnetically separated iron-removed beverage cans, 80 kg of ADC12 waste castings, and recycled aluminum material accounts for 32% of the total mass of metal furnace charge; the remaining components are pure aluminum ingots (650 kg, accounting for 63%), Al-10Cr master alloy (15.5 kg), Al-10La master alloy (3.4 kg), Al-10Ce master alloy (5.3 kg), Al-10Ni master alloy (1.1 kg), Al-5Ti-1B master alloy (10.5 kg), pure magnesium ingots (8.5 kg) and Al-50Cu master alloy (2.6 kg). Ultimately, the actual chemical composition, by mass percentage, is 0.35% Fe, 0.183% Mn, 0.155% Cr, 0.822% Si, 1.06% Mg, 0.25% Cu, 0.03% La, 0.051% Ce, 0.011% Ni, and 0.05% Ti, with the balance being Al and unavoidable trace inclusions.

[0069] The Al-Mg-Si-RE aluminum alloy final forging prepared in this embodiment, after T6 heat treatment, exhibits the following average tensile strength at room temperature. R m Up to 361 MPa, specified plastic elongation strength R p0.2 The strength is 327 MPa, and the elongation after fracture is... A It is 12.6%.

[0070] Comparative Example 1 A low-carbon, high-performance Al-Mg-Si-RE aluminum alloy for forging differs from Example 1 in that the aluminum alloy comprises, by mass percentage: 0.12% Fe, 0.10% Mn, 0.25% Cr, 0.85% Si, 1.05% Mg, 0.25% Cu, 0.02% La, 0.02% Ce, 0.006% Ni, and 0.05% Ti, with the balance being Al and unavoidable trace impurities. The Mg / Si mass ratio is 1.235, the Fe / (Mn+Cr) mass ratio is 0.34, and the sum of the mass percentages of La, Ce, Ni, and Ti is 0.096.

[0071] This comparative example maintains the same overall process flow as Example 1 (covering raw materials, smelting, refining, casting, homogenization, forging, and heat treatment processes), but differs in the addition of Mg and Si elements. Ultimately, the actual chemical composition, by mass percentage, is 0.123% Fe, 0.099% Mn, 0.247% Cr, 0.85% Si, 1.051% Mg, 0.249% Cu, 0.02% La, 0.021% Ce, 0.006% Ni, and 0.051% Ti, with the balance being Al and unavoidable trace inclusions.

[0072] The Al-Mg-Si-RE aluminum alloy final forging prepared in this comparative example, after T6 heat treatment, exhibited an average tensile strength at room temperature. R m Up to 346 MPa, specified plastic elongation strength R p0.2 The strength is 313 MPa, and the elongation after fracture is... A It is 9.2%.

[0073] Comparative Example 2 A low-carbon, high-performance Al-Mg-Si-RE aluminum alloy for forging differs from Example 2 in that the aluminum alloy comprises, by mass percentage: 0.25% Fe, 0.18% Mn, 0.25% Cr, 0.789% Si, 1.20% Mg, 0.25% Cu, 0.03% La, 0.03% Ce, 0.006% Ni, and 0.05% Ti, with the balance being Al and unavoidable trace impurities. The Mg / Si mass ratio is 1.52, the Fe / (Mn+Cr) mass ratio is 0.58, and the sum of the mass percentages of La, Ce, Ni, and Ti is 0.116.

[0074] This comparative example maintains the same overall process flow as Example 2, but differs in the addition of Mg and Si elements. Ultimately, the actual chemical composition, by mass percentage, is 0.254% Fe, 0.181% Mn, 0.248% Cr, 0.789% Si, 1.196% Mg, 0.247% Cu, 0.03% La, 0.031% Ce, 0.006% Ni, and 0.052% Ti, with the balance being Al and unavoidable trace inclusions.

[0075] The Al-Mg-Si-RE aluminum alloy final forging prepared in this comparative example, after T6 heat treatment, exhibited an average tensile strength at room temperature. R m Up to 343 MPa, specified plastic elongation strength R p0.2 The strength is 316 MPa, and the elongation after fracture is... A It is 7.8%.

[0076] Comparative Example 3 A low-carbon, high-performance Al-Mg-Si-RE aluminum alloy for forging differs from Example 2 in that the aluminum alloy comprises, by mass percentage: 0.25% Fe, 0.20% Mn, 0.20% Cr, 0.75% Si, 1.05% Mg, 0.25% Cu, 0.03% La, 0.03% Ce, 0.006% Ni, and 0.05% Ti, with the balance being Al and unavoidable trace impurities. The Mg / Si mass ratio is 1.40, the Fe / (Mn+Cr) mass ratio is 0.625, and the sum of the mass percentages of La, Ce, Ni, and Ti is 0.116.

[0077] This comparative example maintains the same process flow as Example 2, but differs in the addition of Mn and Cr elements. Ultimately, the actual chemical composition, by mass percentage, is 0.254% Fe, 0.204% Mn, 0.202% Cr, 0.751% Si, 1.05% Mg, 0.249% Cu, 0.03% La, 0.031% Ce, 0.006% Ni, and 0.052% Ti, with the balance being Al and unavoidable trace inclusions.

[0078] The Al-Mg-Si-RE aluminum alloy final forging prepared in this comparative example, after T6 heat treatment, exhibited an average tensile strength at room temperature. R m Up to 327 MPa, specified plastic elongation strength R p0.2 The strength is 309 MPa, and the elongation after fracture is... A It is 8.6%.

[0079] Comparative Example 4 A low-carbon, high-performance Al-Mg-Si-RE aluminum alloy for forging differs from Example 5 in that the aluminum alloy comprises, by mass percentage: 0.35% Fe, 0.25% Mn, 0.26% Cr, 0.75% Si, 1.05% Mg, 0.20% Cu, 0.03% La, 0.04% Ce, 0.02% Ni, and 0.06% Ti, with the balance being Al and unavoidable trace impurities. The Mg / Si mass ratio is 1.40, the Fe / (Mn+Cr) mass ratio is 0.686, and the sum of the mass percentages of La, Ce, Ni, and Ti is 0.15.

[0080] This comparative example maintains the same process flow as Example 5, but differs in the addition of Mn and Cr elements. Ultimately, the actual chemical composition, by mass percentage, is 0.35% Fe, 0.249% Mn, 0.259% Cr, 0.749% Si, 1.05% Mg, 0.20% Cu, 0.031% La, 0.03% Ce, 0.02% Ni, and 0.049% Ti, with the balance being Al and unavoidable trace inclusions.

[0081] The Al-Mg-Si-RE aluminum alloy final forging prepared in this comparative example, after T6 heat treatment, exhibited an average tensile strength at room temperature. R m Up to 321 MPa, specified plastic elongation strength R p0.2 The strength is 313 MPa, and the elongation after fracture is... A It is 7.4%.

[0082] Comparative Example 5 A low-carbon, high-performance Al-Mg-Si-RE aluminum alloy for forging differs from Example 5 in that the aluminum alloy comprises, by mass percentage: 0.35% Fe, 0.25% Mn, 0.24% Cr, 0.75% Si, 1.05% Mg, 0.20% Cu, 0.035% La, 0.03% Ce, 0.01% Ni, and 0.05% Ti, with the balance being Al and unavoidable trace impurities. The Mg / Si mass ratio is 1.40, the Fe / (Mn+Cr) mass ratio is 0.714, and the sum of the mass percentages of La, Ce, Ni, and Ti is 0.125.

[0083] This comparative example maintains the same process flow as Example 5, but differs in the addition of La, Ce, Ni, and Ti elements. Ultimately, the actual chemical composition, by mass percentage, is 0.351% Fe, 0.248% Mn, 0.239% Cr, 0.742% Si, 1.045% Mg, 0.20% Cu, 0.035% La, 0.03% Ce, 0.011% Ni, and 0.049% Ti, with the balance being Al and unavoidable trace inclusions.

[0084] The Al-Mg-Si-RE aluminum alloy final forging prepared in this comparative example, after T6 heat treatment, exhibited an average tensile strength at room temperature. R m Up to 318 MPa, specified plastic elongation strength R p0.2 The strength is 310 MPa, and the elongation after fracture is... A It is 7.7%.

[0085] Comparative Example 6 A low-carbon, high-performance Al-Mg-Si-RE aluminum alloy for forging differs from Example 5 in that the aluminum alloy comprises, by mass percentage: 0.35% Fe, 0.25% Mn, 0.24% Cr, 0.75% Si, 1.05% Mg, 0.20% Cu, 0.03% La, 0.04% Ce, 0.05% Ni, and 0.065% Ti, with the balance being Al and unavoidable trace impurities. The Mg / Si mass ratio is 1.40, the Fe / (Mn+Cr) mass ratio is 0.714, and the sum of the mass percentages of La, Ce, Ni, and Ti is 0.185.

[0086] This comparative example maintains the same process flow as Example 5, but differs in the addition of Ni and Ti elements. Ultimately, the actual chemical composition, by mass percentage, is 0.351% Fe, 0.252% Mn, 0.239% Cr, 0.752% Si, 1.054% Mg, 0.20% Cu, 0.03% La, 0.04% Ce, 0.05% Ni, and 0.065% Ti, with the balance being Al and unavoidable trace inclusions.

[0087] The Al-Mg-Si-RE aluminum alloy final forging prepared in this comparative example, after T6 heat treatment, exhibited an average tensile strength at room temperature. R m Up to 316 MPa, specified plastic elongation strength R p0.2 The strength is 308 MPa, and the elongation after fracture is... A It is 7.1%.

[0088] Table 2 lists the room temperature tensile properties of Al-Mg-Si-RE aluminum alloy forgings (T6 heat treatment) in the examples and comparative examples.

[0089] Table 2. Room temperature tensile properties of forgings (treated with T6 heat treatment) in the examples and comparative examples.

[0090] As shown in Table 2, the Al-Mg-Si-RE aluminum alloy forgings (after T6 heat treatment) prepared in Examples 1-7 all achieved excellent room temperature tensile properties: average tensile strength R m ≥350MPa, specified plastic elongation strength R p0.2 ≥315MPa, elongation after fracture A ≥12%. Crucially, even when recycled aluminum accounts for 50% of the total feed mass, the above performance levels are consistently maintained in all embodiments. This result fully verifies that the rare-earth microalloying system, the synergistic control strategy for impurity elements, and the suitable preparation process designed in this invention can effectively suppress the coarsening and segregation of high-Fe impurity phases in recycled aluminum, ensuring microstructure uniformity and interfacial bonding strength, thereby endowing the material with high-performance stability and scalable manufacturing feasibility under the constraint of low-carbon raw materials.

[0091] In contrast, the room temperature tensile properties of the Al-Mg-Si-RE aluminum alloy forgings prepared in Comparative Examples 1-6 showed a systematic deterioration, especially in elongation after fracture. A The most significant decrease was observed in the elongation at break of most samples. A The percentage of 7% to 9% indicates that its composition design or process parameters deviate from the key technology boundary of this invention, making it difficult to meet the basic requirements of automotive structural components for a coordinated match between strength and toughness.

[0092] The microstructure of the forging obtained in Example 2 (T6 state) was characterized by microstructure, and the results are as follows: Figure 1 As shown, optical metallographic observation indicates that the second phase in the matrix is ​​mainly composed of fine, dispersed spherical and ellipsoidal particles; no continuous network precipitates, coarse needle-like or platy second phases were found in this observation area. Figure 2High-resolution HAADF-STEM images and corresponding EDS surface scan elemental distribution maps of the same sample prepared by ion thinning are shown. The results indicate that the Fe-containing phase mainly exists as a nanoscale Al(Fe / Mn / Cr)Si composite phase, exhibiting a spherical, dispersed distribution with an equivalent diameter concentrated in the 100 nm–200 nm range. Significant co-segregation of Fe, Mn, and Cr elements is also observed. This nanoscale phase has clear interfaces, a complete crystal structure, and no obvious amorphous shell or compositional gradient. This highly dispersed, size-controllable iron-rich phase not only significantly reduces the tearing effect of traditional coarse needle-like / blocky iron-rich phases on plastic deformation but also provides effective dispersion strengthening through the Orowan bypass mechanism, thereby achieving a synergistic improvement in strength and toughness.

[0093] The fine, uniform microstructure without significant segregation exhibited in Example 2 is highly consistent with its excellent measured mechanical properties. This leap in overall performance stems from a multi-scale synergistic control process system. The synergistic effect of the aforementioned process chain effectively suppresses the segregation tendency of Fe in recycled aluminum, promoting the transformation of the iron-rich phase from coarse, blocky or needle-like structures into dispersed nanoparticles with a sphericity ≥85% and an equivalent diameter concentrated in the range of 100 nm to 200 nm. This significantly weakens the pinning effect on dislocation slip and the hindering effect on grain boundary migration, thereby maintaining high specified ductile elongation strength. R p0.2 At the same time, it significantly improves the material's uniform elongation and fracture toughness, ultimately achieving simultaneous optimization of strength and toughness indicators and ensuring engineering manufacturability.

[0094] Compared to Example 1 (Mg / Si mass ratio = 1.40), the Mg / Si mass ratio of Comparative Example 1 was 1.235, which is lower than the lower limit of the process window defined in this invention (1.25); compared to Example 2 (Mg / Si mass ratio = 1.40), the Mg / Si mass ratio of Comparative Example 2 was 1.52, which exceeds the upper limit of the process window defined in this invention (1.50). This compositional deviation directly leads to an imbalance in the precipitation kinetics of the Mg2Si phase: when the ratio is too low, the number of precipitated phases is insufficient and the dispersion decreases; when the ratio is too high, it induces the precipitation of coarse Mg2Si phases and silicon-rich eutectic phases along grain boundaries. Its macroscopic mechanical response is manifested in the elongation after fracture. A The plastic elongation strength was significantly reduced from 13.8% to 14.3% in the examples to 7.8% to 9.2%, with the specified plastic elongation strength... R p0.2 and tensile strength R m The values ​​also decreased, indicating that the Mg / Si ratio has a high sensitivity and threshold effect on the regulation of strength-toughness synergy.

[0095] Compared with Example 2 (Fe / (Mn+Cr)=0.58), the ratio of Fe / (Mn+Cr) in Comparative Example 3 is 0.625, which is higher than the upper limit threshold (0.6) set by the present invention. Figure 3 High-resolution HAADF-STEM images and corresponding EDS surface scan elemental distribution maps of the iron-rich phase in the Al-Mg-Si-RE aluminum alloy forging (T6 treatment) prepared in Comparative Example 3 are shown. The results indicate that due to the deviation of the Fe, Mn, and Cr elemental ratio from the optimal synergistic window, a large number of coarse-sized, blocky iron-rich phases (single-phase size approximately 1.5 μm–3 μm) precipitated in the aluminum matrix. EDS compositional analysis shows that this phase is also an Al(Fe / Mn / Cr)Si composite intermetallic compound. These coarse and brittle phases not only fail to provide effective precipitation strengthening but also easily disrupt the matrix continuity, becoming the core sites for preferential microcrack initiation and propagation under stress, thus affecting the alloy's elongation after fracture. A The Fe / (Mn+Cr) ratio decreased significantly. This indicates that the Fe / (Mn+Cr) ratio plays a crucial regulatory role in the evolution of the iron-rich phase morphology and the matching performance of strength and toughness. Compared with Example 5, the Fe / (Mn+Cr) ratio in Comparative Example 4 was 0.686, which is lower than the lower limit threshold (0.70) set by this invention, also leading to the precipitation of large-sized iron-rich phases and deteriorating the strength and toughness of the material.

[0096] Compared with Example 5, the total mass fractions of La+Ce+Ni+Ti in Comparative Examples 5 and 6 were 0.125 and 0.185, respectively, both of which deviated from the optimized process window (0.13-0.18) defined in this invention. Figure 4 High-resolution HAADF-STEM images and corresponding EDS surface scan elemental distribution maps of the iron-rich phase and rare earth phase in the Al-Mg-Si-RE aluminum alloy forging (T6 state) prepared in Comparative Example 6 are shown. The results indicate that when the RE(La+Ce)+Ni+Ti content is below the lower limit (0.125), it is insufficient to fully suppress the coarsening of the iron-rich phase; when it is above the upper limit (0.185), excess rare earth elements promote interfacial reactions between RE and the iron-rich phase, generating brittle, strip-shaped Al(Fe / Mn / Cr)Si-La / Ce / Ni composite phases. Both types of deviations disrupt the continuity of the matrix structure, fragment the matrix, and thus significantly reduce the plasticity and toughness of the forging.

[0097] The embodiments of the present invention have been described above with reference to the accompanying drawings. However, the present invention is not limited to the specific embodiments described above. The specific embodiments described above are merely illustrative and not restrictive. Those skilled in the art can make many other forms under the guidance of the present invention without departing from the spirit and scope of the claims, and all of these forms fall within the scope of protection of the present invention.

Claims

1. A low-carbon, high-performance Al-Mg-Si-RE aluminum alloy for forging, characterized in that, The chemical composition, by mass fraction, includes: Si: 0.60%–0.90%, Mg: 0.90%–1.20%, Cu: 0.15%–0.30%, Fe: 0.12%–0.40%, Mn: 0.05%–0.25%, Cr: 0.15%–0.30%, La: 0.02%–0.10%, Ce: 0.02%–0.10%, Ni: 0.003%–0.05%, Ti: 0.03%–0.10%, with the balance being Al and unavoidable trace impurities; and meets the following requirements. The following proportions are constrained: the mass ratio of Mg to Si is 1.25–1.50; when the Fe content is 0.12%–0.30%, the mass ratio of Fe to (Mn+Cr) is 0.31–0.60, and the total mass fraction of La, Ce, Ni, and Ti is 0.08%–0.12%; when the Fe content is greater than 0.30% and not greater than 0.40%, the mass ratio of Fe to (Mn+Cr) is 0.70–1.05, and the total mass fraction of La, Ce, Ni, and Ti is 0.13%–0.18%.

2. The low-carbon, high-performance Al-Mg-Si-RE aluminum alloy for forging according to claim 1, characterized in that, By mass fraction, Si is 0.65%–0.85%, Mg is 0.95%–1.15%, and Cu is 0.18%–0.28%.

3. The low-carbon, high-performance Al-Mg-Si-RE aluminum alloy for forging according to claim 1, characterized in that, The aluminum alloy is produced by smelting a furnace charge containing a base aluminum source and recycled aluminum, wherein the proportion of recycled aluminum in the total mass of the furnace charge is ≥50%; the base aluminum source is electrolytic aluminum liquid or high-purity aluminum ingot, and the recycled aluminum includes at least two of the following: waste beverage cans, waste 6-series profiles, and ADC12 die-casting waste.

4. The low-carbon, high-performance Al-Mg-Si-RE aluminum alloy for forging according to claim 1, characterized in that, In the forged alloy after T6 heat treatment, the iron-rich phase consists of near-spherical α-Al(Fe / Mn / Cr)Si dispersed particles with an equivalent diameter of 100nm to 200nm, the spheroidization rate of the iron-rich phase is ≥85%, and the aspect ratio of the iron-rich phase is ≤3:

1.

5. The low-carbon, high-performance Al-Mg-Si-RE aluminum alloy for forging according to claim 1, characterized in that, The forged alloy treated with T6 heat meets the following mechanical properties: when the Fe content is 0.12% to 0.30%, the tensile strength is... R m ≥350MPa, specified plastic elongation strength R p0.2 ≥315MPa, elongation after fracture A ≥13%; when the Fe content is greater than 0.30% and not greater than 0.40%, tensile strength R m ≥350MPa, specified plastic elongation strength R p0.2 ≥320MPa, elongation after fracture A ≥12%.

6. The low-carbon, high-performance Al-Mg-Si-RE aluminum alloy for forging according to claim 1, characterized in that, When the Fe content is 0.12% to 0.30%, the mass ratio of Fe to (Mn+Cr) is 0.34 to 0.60, and the total mass fraction of La, Ce, Ni and Ti is 0.09% to 0.12%.

7. The low-carbon, high-performance Al-Mg-Si-RE aluminum alloy for forging according to claim 1, characterized in that, When the Fe content is greater than 0.30% and not greater than 0.40%, the mass ratio of Fe to (Mn+Cr) is 0.71 to 1.04, and the total mass fraction of La, Ce, Ni and Ti is 0.14% to 0.18%.

8. A method for preparing a low-carbon, high-performance Al-Mg-Si-RE aluminum alloy for forging according to any one of claims 1 to 7, characterized in that, Includes the following steps: (1) Raw material pretreatment: Different types of recycled aluminum raw materials are sorted and cleaned, surface cleaned, crushed, magnetically separated to remove iron, and then pressed into blocks for use; among them, surface cleansing includes paint removal or degreasing treatment depending on the type of raw material; (2) Melting and refining: First, melt the basic aluminum source and some recycled aluminum raw materials to form a molten pool. Add recycled aluminum briquettes in batches. After electromagnetic stirring until uniform, add intermediate alloy to adjust the composition. Finally, add pure magnesium. Then, refine by powder spraying, degas by argon rotary blowing, remove slag and let stand. The refining temperature is 730℃~750℃. Before casting, add Al-Ti-B intermediate alloy online in the trough to refine the grains. (3) Vertical semi-continuous casting: After the melt is degassed online and filtered through a double-stage depth filter of ceramic filter plate and tubular filter, forged round ingots are prepared at a casting temperature of 720℃~740℃ and a casting speed of (75~100) mm / min. (4) Homogenization treatment: The round ingot is subjected to a three-stage homogenization treatment, and then cooled at a controlled rate after being kept at 540℃~560℃ for 10h~12h. (5) Forging process: After the ingot is preheated at 430℃~470℃ for 1.5h~2.5h, it is formed by three steps of closed die forging: pre-forging billet preparation, precision forging, and correction and shaping. The final forging temperature is controlled at 380℃~420℃. (6) T6 heat treatment: The forging is solution heat-held at 530℃~540℃ for 4h~6h and then quenched, followed by single-stage aging heat-held at 170℃~190℃ for 4h~8h and air-cooled to obtain the finished product.

9. The method for preparing the low-carbon, high-performance Al-Mg-Si-RE aluminum alloy for forging according to claim 8, characterized in that, The three-stage homogenization process in step (4) is as follows: the temperature is gradually increased to 540℃~560℃ and held for 10 h~12 h; after the holding period, segmented controllable cooling is carried out, first cooling to 300℃ at a rate of (100~300)℃ / h, and then slowly cooling to below 150℃ with the furnace before being taken out of the furnace.

10. The method for preparing the low-carbon, high-performance Al-Mg-Si-RE aluminum alloy for forging according to claim 8, characterized in that, In step (5), a forging press of 8000t to 10000t is used for pre-forging, a forging press of 4000t to 6000t is used for precision forging, and an 800t forging press is used for correction and shaping. The average temperature drop rate during the forging process is ≤5℃ / s, and the fluctuation range of the local temperature drop rate is controlled within ±0.8℃ / s.